2023
DOI: 10.3389/fphys.2023.1221898
|View full text |Cite
|
Sign up to set email alerts
|

Effect of exercise intervention on smoking cessation: a meta-analysis

Abstract: Background: Exercise has emerged as an effective approach to promote individual health and has shown potential in aiding smoking cessation. However, the specific benefits of exercise in smoking cessation remain unclear, and conflicting findings across studies may be attributed to variations in study populations and intervention characteristics. This study aims to conduct a meta-analysis to evaluate the impact of exercise interventions on tobacco dependence in smokers and assess the effectiveness of exercise in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 76 publications
0
1
0
Order By: Relevance
“…Exercise is a non-pharmacological intervention for smoking cessation, given its capacity to alleviate withdrawal symptoms and cravings. A recent systematic review has indicated that aerobic exercises exceeding 10 minutes reduce the desire to smoke, and moderate to high-intensity aerobic exercises significantly reduce the strength of this desire 5 . Additionally, short-bout (5-10 min) isometric exercise, which involves maintaining a static muscle contraction without moving the affected joint, is also effective in relieving withdrawal symptoms 6,7 , suggesting a spectrum of exercise durations and intensities is beneficial in smoking cessation.…”
Section: Introductionmentioning
confidence: 99%
“…Exercise is a non-pharmacological intervention for smoking cessation, given its capacity to alleviate withdrawal symptoms and cravings. A recent systematic review has indicated that aerobic exercises exceeding 10 minutes reduce the desire to smoke, and moderate to high-intensity aerobic exercises significantly reduce the strength of this desire 5 . Additionally, short-bout (5-10 min) isometric exercise, which involves maintaining a static muscle contraction without moving the affected joint, is also effective in relieving withdrawal symptoms 6,7 , suggesting a spectrum of exercise durations and intensities is beneficial in smoking cessation.…”
Section: Introductionmentioning
confidence: 99%